Early Predictors and Correlates of Communication Function in Children With Cerebral Palsy. (March 2018) - Hidecker, Mary Jo Cooley; Slaughter, Jaime; Abeysekara, Purni; Ho, Nhan T.; Dodge, Nancy; Hurvitz, Edward A.; Workinger, Marilyn Seif; Kent, Ray D.; Rosenbaum, Peter; Lenski, Madeleine; Vanderbeek, Suzette Báez; DeRoos, Steven; et al.
Birth characteristics and developmental milestones were evaluated as early predictors/correlates of communication in children with cerebral palsy. The hypothesis was that maternal report of child's age for vocal play and first words would predict current functional communication. A case series of 215 children, 2 to 17 years (mean age = 8.2 years, SD = 3.9) with cerebral palsy was recruited from medical practices in 3 Michigan cities. Early developmental data were collected by maternal interview. The child's Communication Function Classification System (CFCS) level was obtained from parent. Predictors of less functional communication included gestational age >32 weeks, number of comorbidities, age of first words after age 24 months, and use of communication methods other than speech. Several birth characteristics and developmental language milestones were predictive of later communication performance for children with cerebral palsy. These characteristics and milestones should trigger referrals for communication evaluations, including speech, language, hearing, and/or augmentative and alternative communication.